The loss of βΙ spectrin alters synaptic size and composition in the ja/ja mouse - Stankewich, Michael C.; Peters, Luanne L.; Morrow, Jon S. (Frontiers in Neuroscience, 2024)
Introduction: Deletion or mutation of members of the spectrin gene family contributes to many neurologic and neuropsychiatric disorders. While each spectrinopathy may generate distinct neuropathology, the study of bI spectrin's role (Sptb) in the brain has been hampered by the hematologic consequences of its loss.Methods: Jaundiced mice (ja/ja) that lack bI spectrin suffer a rapidly fatal hemolytic anemia. We have used exchange transfusion of newborn ja/ja mice to blunt their hemolytic pathology, enabling an examination of bI spectrin deficiency in the mature mouse brain by ultrastructural and biochemical analysis.Results: bI spectrin is widely utilized throughout the brain as the bIS2 isoform; it appears by postnatal day 8, and concentrates in the CA1,3 region of the hippocampus, dentate gyrus, cerebellar granule layer, cortical layer 2, medial habenula, and ventral thalamus. It is present in a subset of dendrites and absent in white matter. Without bI spectrin there is a 20% reduction in postsynaptic density size in the granule layer of the cerebellum, a selective loss of ankyrinR in cerebellar granule neurons, and a reduction in the level of the postsynaptic adhesion molecule NCAM. While we find no substitution of another spectrin for bI at dendrites or synapses, there is curiously enhanced bIV spectrin expression in the ja/ja brain.